Managing The Invisible Product: A Strategic Framework for Geospatial Infrastructure Investment in Indonesian Ride-Hailing Platform - Muhammad Iqnaul Haq; Aldianto, Leo (Integrasi Sains Media, 2026)
Geospatial capabilities have become critical dependencies in ride-hailing platforms, providing maps, routing, and location services. However, these foundational technologies frequently face prioritization challenges against more visible product features. This research addresses the